The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1155/2019/2196578
|View full text |Cite
|
Sign up to set email alerts
|

Morris Sensitivity Analysis for Hydrothermal Coupling Parameters of Embankment Dam: A Case Study

Abstract: Recently, the use of the temperature tracer method has attracted a great deal of attention to study the dam leakage. Accurate estimation of temperature variations inside the dam is critical, and the task can be achieved by identifying which variables play more important roles in the hydrothermal coupling model (HTCM). In the present study, the HTCM of an embankment dam is defined based on the thermal conductivity model proposed by Lu et al. (2007). The thermal conductivity model needs several input parameters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…A large number of applications in civil engineering relate to groundwater flow, such as slope stability [21][22][23]; surface/subsurface soil erosion and sediment transport [24][25][26]; dam safety, including piping under and through dams [27][28][29][30][31][32]; groundwater contamination [33][34][35][36]; stability of artificially freezing ground [37,38]; sustainable management of water resources [39][40][41][42]; interaction between groundwater and surface water [43,44]; and karst collapse pillars [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of applications in civil engineering relate to groundwater flow, such as slope stability [21][22][23]; surface/subsurface soil erosion and sediment transport [24][25][26]; dam safety, including piping under and through dams [27][28][29][30][31][32]; groundwater contamination [33][34][35][36]; stability of artificially freezing ground [37,38]; sustainable management of water resources [39][40][41][42]; interaction between groundwater and surface water [43,44]; and karst collapse pillars [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results in Table 4, the average RMSE, R 2 , and Re values for the Ren model, Lu model, and Côté and Konrad model were 0.86°C, 0.95, and 3.57%, respectively, and each evaluation index reflected a satisfactory result. e Lu model is a thermal conductivity model that has been widely used in recent years [43,44] and provides a good simulation effect [18]. Research by Ren et al [18] revealed that coupled hydrothermal modeling based on the Lu model yielded better results than the traditional modeling technique, suggesting that changes in the equivalent thermal conductivity model can promote the accuracy of coupled riparian zone modeling.…”
Section: Evaluation Of the Simulation Results Of Different Equivalent Ermal Conductivity Modelsmentioning
confidence: 99%
“…The Morris method [24] is a type of screening method, which is suitable for nonlinear models with a large number of factors, and the calculation speed is fast. At the same time, the improved Morris index can also be quantitatively analyzed.…”
Section: Morris Sensitivity Analysis Methodsmentioning
confidence: 99%